The Role of Guidance and Counseling Teachers in Students' Career Planning Using the Career Tree at SMP Santo Aloysius Turi - Axel Obed Chrismanto (CV. Edujavare Publishing, 2026)
This study examines the role of Guidance and Counseling (GC) teachers in supporting students’ career planning through the use of the Career Tree as a guidance medium at Santo Aloysius Turi Middle School. The research aims to explore how GC teachers facilitate students in recognizing their interests, talents, abilities, and future career aspirations while enhancing their career decision-making skills. A qualitative descriptive approach was employed, with data collected through interviews, observations, and documentation involving Guidance and Counseling teachers and students. The findings indicate that the Career Tree serves as an interactive and student-centered guidance tool that encourages self-reflection, career exploration, and active participation in career planning activities. GC teachers play a significant role as facilitators, motivators, and counselors by providing career information, guiding self-assessment, and helping students connect their personal potential with educational and occupational opportunities. Furthermore, the implementation of the Career Tree improves students’ career awareness, confidence, and readiness to make informed educational and career decisions. Despite challenges such as limited guidance time and varying levels of student engagement, the innovative use of the Career Tree contributes positively to the effectiveness of career guidance services. Therefore, integrating creative guidance media into school counseling programs is recommended to strengthen students’ career planning competencies and support their long-term personal and professional development